Fructosamine: An Essential Biomarker in the Diabetes Landscape - G. Vigneswaran (International Journal of Pharmaceutical & Biological Archive, 2024)
Diabetes mellitus is a prevalent metabolic disorder that can lead to severe complications if left untreated, largely due to chronic hyperglycemia. Effective diabetes management requires accurate blood glucose monitoring and reliable diagnostic tools. While hemoglobin A1c (HbA1c) is the gold standard for assessing long-term glycemic control, it has limitations, particularly in individuals with conditions affecting red blood cell turnover. Fructosamine offers an alternative, reflecting average blood glucose levels over the previous 2–3 weeks, providing short-term glycemic management insights. This review explores the role of fructosamine in diagnosing and managing diabetes, comparing its effectiveness to the widely used HbA1c test. It focuses on its applicability in specific patient groups, such as those with hemoglobinopathies, chronic kidney disease, and pregnant women. A comprehensive literature review of clinical studies and guidelines was conducted to evaluate fructosamine’s diagnostic accuracy, its comparison with HbA1c, and its utility in these special populations. Fructosamine effectively measures glycemic control when HbA1c may be unreliable, offering a cost-effective tool that captures short-term glucose fluctuations. However, its accuracy can be influenced by factors like serum protein levels and inconsistencies in testing methods, indicating a need for further standardization. It concludes that fructosamine is a valuable biomarker for short-term glycemic monitoring, particularly in cases where HbA1c may not provide reliable results. Although it is not yet widely adopted as a primary diagnostic tool, fructosamine holds promise as a complement to HbA1c in the diagnosis and management of diabetes, especially in cases requiring rapid assessment of glycemic changes.